2021
DOI: 10.1126/sciadv.abg0868
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of enantiomorphs for the chiral allotrope β-Mn by diffraction methods

Abstract: The assignment of enantiomorphs by diffraction methods shows fundamental differences for x-rays and electrons. This is particularly evident for the chiral allotrope of β-Mn. While it is not possible to determine the sense of chirality of β-Mn with established x-ray diffraction methods, Kikuchi pattern simulation of the enantiomorphs reveals differences, if dynamical electron diffraction is considered. Quantitative comparison between experimental and simulated Kikuchi patterns allows the spatially resolved assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
(56 reference statements)
2
10
0
Order By: Relevance
“…We found that CCs contribute <20% of Earth's K, equivalent to a maximum contribution of ~13% to Earth by mass over all elements (assuming no volatile loss during or after delivery). This is consistent with previous estimates of several percent to 10% by mass (33,34), suggesting that Earth's K has a predominant NC origin. The small contribution of CCs for K and other elements (33,34) is incompatible with a pebble accretion origin of rocky planets (5,35), but is consistent with the hypothesis that dustdrift barriers separated the CC and NC reservoirs from each other (25,26,34).…”
Section: Origin Of Earth's Ksupporting
confidence: 93%
See 1 more Smart Citation
“…We found that CCs contribute <20% of Earth's K, equivalent to a maximum contribution of ~13% to Earth by mass over all elements (assuming no volatile loss during or after delivery). This is consistent with previous estimates of several percent to 10% by mass (33,34), suggesting that Earth's K has a predominant NC origin. The small contribution of CCs for K and other elements (33,34) is incompatible with a pebble accretion origin of rocky planets (5,35), but is consistent with the hypothesis that dustdrift barriers separated the CC and NC reservoirs from each other (25,26,34).…”
Section: Origin Of Earth's Ksupporting
confidence: 93%
“…This is consistent with previous estimates of several percent to 10% by mass (33,34), suggesting that Earth's K has a predominant NC origin. The small contribution of CCs for K and other elements (33,34) is incompatible with a pebble accretion origin of rocky planets (5,35), but is consistent with the hypothesis that dustdrift barriers separated the CC and NC reservoirs from each other (25,26,34). (A) Because the CM group has e 40 K = 0.42 ± 0.99, which overlaps with that of the Earth, any fraction of K from CMs is allowed.…”
Section: Origin Of Earth's Ksupporting
confidence: 93%
“…For β-Mn, we can thus conclude that a reliable assignment of the sense of chirality is possible using Kikuchi diffraction patterns measured in the SEM. Furthermore, this also applies to multi-element compounds with the β-Mn structure type, for which the sense of chirality can be confirmed by X-ray diffraction using anomalous scattering effects [42].…”
Section: Chirality Dependent Kikuchi Diffraction Pattern Matchingmentioning
confidence: 95%
“…Aiming to explore new potential thermoelectric materials with ultralow lattice thermal conductivity, we found a group of ternary tellurides with a structural organization similar to the β-Mn structure. These filled β-manganese-type phases have the chemical composition M 2/ n n + Tr 6 3+ Q 10 2– ( M n+ : Li + , Na + , Ag + , Ca 2+ , Sn 2+ , Pb 2+ , Yb 2+ ; Tr 3 + : Al 3+ , Ga 3+ , In 3+ ; Q 2– : Se 2– , Te 2– ) and are characterized by close packings of Q 4 -tetrahedra, which is similar to the arrangement of manganese atoms in the cubic β-Mn. When M + ions fill all available distorted octahedral voids, the M 2+ ions occupy only half of them, and Tr 3+ ions are distributed in an ordered wayover 15% of the tetrahedral voids.…”
Section: Introductionmentioning
confidence: 99%